2020
DOI: 10.1002/pds.5037
|View full text |Cite
|
Sign up to set email alerts
|

Using negative control outcomes to assess the comparability of treatment groups among women with osteoporosis in the United States

Abstract: PurposeIn contrast to randomized clinical trials, comparative safety and effectiveness assessments of osteoporosis medications in clinical practice may be subject to confounding by indication. We used negative control outcomes to detect residual confounding when comparing osteoporosis medications.MethodsUsing MarketScan Commercial and Supplemental claims, we identified women aged ≥55 years who initiated an oral bisphosphonate (BP) (risedronate, alendronate, or ibandronate), denosumab (an injected biologic), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…We then used the null distribution to compute the calibrated P value and confidence intervals. This approach has been used in many previous studies in different clinical areas, including covid-19 repurposed treatments, 34 35 36 and was acknowledged in the latest version of the ENCePP guide on methodological standards in pharmacoepidemiology. 37 We only presented estimates specific to databases where empirical calibrations were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…We then used the null distribution to compute the calibrated P value and confidence intervals. This approach has been used in many previous studies in different clinical areas, including covid-19 repurposed treatments, 34 35 36 and was acknowledged in the latest version of the ENCePP guide on methodological standards in pharmacoepidemiology. 37 We only presented estimates specific to databases where empirical calibrations were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the first 3 months after treatment initiation were chosen to represent the baseline fracture risk: prior clinical studies have shown little difference in the incidence of fracture outcomes between denosumab and placebo for at least 6 months after treatment initiation [ 21 ]. Furthermore, recent studies have used fractures occurring in the first 3 months as ‘negative control outcomes’ to detect residual confounding on the assumption that there is no measurable treatment effect on fracture within the first 3 months and that this, therefore, represents a measure of baseline fracture risk [ 28 ]. In this real-world study, using this within-cohort approach, these data show that continued treatment with osteoporosis medications is associated with reductions of fracture rates in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…An expert panel reviewed possible mechanisms of confounding in the study population and selected 10 negative control outcomes: four associated with frailty (decubitus ulcer, accident, fracture, and cancer, excluding nonmelanoma skin cancer) and six associated with health‐seeking behaviors (wellness visit, visual test, influenza vaccine, herpes zoster or pneumococcal vaccine, colon cancer screening, and nonmelanoma skin cancer or Mohs surgery). The majority of negative control outcomes were modeled after those developed in our prior work 16 . An exception was the cancer outcome, which was hypothesized to be associated with frailty given previous findings of high levels of frailty indicators in both older and younger adults diagnosed with cancer 17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, if the outcome of interest for a comparative effectiveness study of LLT regimens was MI, the ideal negative control outcomes would share a confounding structure with treatment selection (i.e., PCSK9i vs. ezetimibe or high‐intensity statin) and MI. Outcomes used in prior negative control studies include decubitus ulcer and accidents (i.e., confounding by disease severity or frailty), and wellness visits, vaccinations, and cancer screenings (i.e., confounding by health‐seeking behaviors) 13–16 …”
Section: Introductionmentioning
confidence: 99%